Analysis of Operational Risk Management in the BAZNAS RI Scholarsip Program - Rahman, Abdul; Suryadi, Eko (Li Falah: Journal of Islamic Economics and Business, 2026)
The surge in the distribution of Zakat, Infaq, and Alms (ZIS) BAZNAS RI funds in the education sector for the 2021-2025 period, which grew exponentially to reach IDR 308 billion, requires accountable governance to avoid operational risks. This research aims to analyze in depth the process and effectiveness of the implementation of operational risk management in the BAZNAS RI Scholarship Program. Using a descriptive-analytical qualitative approach, primary data was collected through in-depth interviews with the Head of the Education and Da'wah Division and the implementing staff, supported by secondary data in the form of monthly financial statements and SOP documents. Data analysis refers to the interactive model of Miles, Huberman, and Saldaña with triangulation techniques for data validity. The results of the study show that BAZNAS RI has adopted the ISO 31000 standard through four main stages: risk identification, risk measurement/analysis, risk mitigation, and monitoring. The main risk clusters include selection (input) risk, distribution process (process) risk, and evaluation (output) risk. The effectiveness of mitigation is strengthened through multi-layered factual verification instruments, mentoring and periodic coaching systems, and digitization of information systems. However, strengthening the consistency of internalizing a risk awareness culture at the level of frontline implementing staff is still a major challenge that must be perfected in order to maintain public trust in a sustainable manner.